PENERAPAN MODEL PEMBELAJARAN SDL (SELF DIRECTED LEARNING) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA - NUR KHOTIMAH (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2022)
The purpose of this study was to determine the effect of learning activities, increase in learning outcomes after implementing SDL (Self Directed Learning) learning in class VII C students of SMP Negeri 1 Babat in the odd semester of the 2022/2023 school year. The type of research conducted was classroom action research ) From the results of student learning, namely in the final test results of cycle II there was an increase from cycle I, namely as many as 26 students had completed learning so that mastery increased by 3%. Based on observations of researchers in cycle II, (1) students had started to be active in group activities but not optimal, (2) students have started to give a positive response to learning by working on worksheets but not optimal in using visual aids.Based on the observations of researchers in cycle III, there was an increase from cycle II, namely as many as 30 students had completed learning so that completeness increased by 13% (1) students have started to be active in k group activities and have dared to present in front of the class, (2) students have given positive and independent responses in working on worksheets and using teaching aids (3) students are motivated and interested in taking lessons. ABSTRAKTujuan penelitian ini adalah mengetahui pengaruh aktivitas belajar, peningkatan hasil belajar setelah diterapkanya pembelajaran SDL (Self Directed Learning pada siswa kelas VII C SMP Negeri 1 Babat pada semester ganjil tahun pelajaran 2022/2023. Jenis penelitian yang dilakukan adalah penelitian tindakan kelas (classroom action research). Dari hasil belajar siswa yaitu pada hasil tes akhir siklus II terdapat peningkatan dari siklus I yaitu sebanyak 26 siswa telah tuntas belajar sehingga ketuntasan meningkat sebesar 3 %. Berdasarkan pengamatan peneliti pada siklus II, (1) siswa sudah mulai aktif dalam kegiatan kelompok tapi belum maksimal , (2) siswa sudah mulai memberikan respon positif terhadap pembelajaran dengan mengerjakan LKS tapi belum maksimal dalam menggunakan alat peraga. Berdasarkan pengamatan peneliti pada siklus III, terdapat peningkatan dari siklus II yaitu sebanyak 30 siswa telah tuntas belajar sehingga ketuntasan meningkat sebesar 13 %. (1) siswa sudah mulai aktif dalam kegiatan kelompok dan sudah berani presentasi ke depan kelas , (2) siswa sudah memberikan respon positif dan mandiri dalam mengerjakan LKS dan menggunakan alat peraga (3) Siswa sudah termotivasi dan berminat mengikuti pelajaran.